Insights into Diversity, Distribution, and Systematics of Rust Genus Puccinia - Shubhi Avasthi; Ajay Kumar Gautam; Mekala Niranjan; Rajnish Kumar Verma; Samantha C. Karunarathna; Ashwani Kumar; Nakarin Suwannarach (Journal of Fungi, 2023)
Puccinia, which comprises 4000 species, is the largest genus of rust fungi and one of the destructive plant pathogenic rust genera that are reported to infect both agricultural and nonagricultural plants with severe illnesses. The presence of bi-celled teliospores is one of the major features of these rust fungi that differentiated them from Uromyces, which is another largest genus of rust fungi. In the present study, an overview of the current knowledge on the general taxonomy and ecology of the rust genus Puccinia is presented. The status of the molecular identification of this genus along with updated species numbers and their current statuses in the 21st century are also presented, in addition to their threats to both agricultural and nonagricultural plants. Furthermore, a phylogenetic analysis based on ITS and LSU DNA sequence data available in GenBank and the published literature was performed to examine the intergeneric relationships of Puccinia. The obtained results revealed the worldwide distribution of Puccinia. Compared with other nations, a reasonable increase in research publications over the current century was demonstrated in Asian countries. The plant families Asteraceae and Poaceae were observed as the most infected in the 21st century. The phylogenetic studies of the LSU and ITS sequence data revealed the polyphyletic nature of Puccinia. In addition, the presences of too short, too lengthy, and incomplete sequences in the NCBI database demonstrate the need for extensive DNA-based analyses for a better understanding of the taxonomic placement of Puccinia.